Draft Genome Sequence of the Industrially Significant Bacterium Bacillus amyloliquefaciens NRRL 942 - Meier, Matthew J. (Microbiol Resour Announc, 2018)
Bacillus amyloliquefaciens NRRL 942 is a Gram-positive bacterium with several potential industrial uses. We have sequenced the whole genome of this organism to assist in understanding the biological mechanisms that might modulate human health or environmental risk in the event of its release into the environment.